Cognitive Leap or Digital Divide? A Comparative Study on AI-Driven Learning and Student Analytical Capacity in Samarinda and Aceh - Anita, Anita; Mulawarman, Widyatmike Gede; Susilo, Susilo (Jurnal Pendidikan Progresif, 2025)
Cognitive Leap or Digital Divide? A Comparative Study on AI-Driven Learning and Student Analytical Capacity in Samarinda and Aceh. Objective: The purpose of this study is to investigate the impact of artificial intelligence (AI) on teaching methods on students' analytical thinking abilities in Aceh and Samarinda, two distinct regions of Indonesia. This study explores whether AI functions as a reflective cognitive stimulant or simply as a way to speed up students' assignments. Method: This study employed a descriptive qualitative analysis, utilizing data collection methods such as semi-structured interviews with 80 participants, comprising 20 teachers and 60 high school students from Aceh and Samarinda. In addition, analytical tools such as NVivo 14 also supported the data management process, such as selective, axial, and open coding. Purposive sampling was used to select participants representing diverse educational environments and varying digital literacy levels. Through researcher triangulation, peer debriefing, and member checking, thematic saturation was ensured, and rigor was upheld. Findings: The results show significant regional variations in the use of AI. AI is utilized as a tool for introspection, argument construction, and investigation of various viewpoints in Samarinda, where educators demonstrate higher levels of digital and pedagogical literacy. Students actively utilize ChatGPT and related sites to develop their critical thinking skills. On the other hand, due to a lack of teacher supervision and limited exposure to technology, AI is primarily used in Aceh to automate tasks with minimal critical engagement. Students often turn to AI for quick responses, which can hinder their ability to think critically and develop their analytical skills. Conclusion: This study concluded that the quality of teacher mediation and the pedagogical context have a greater influence on students' analytical abilities than access to technology. Reflective learning techniques, teacher digital competence, and an educational culture that prioritizes critical thinking over task completion are all necessary for effective AI integration. Keywords: artificial intelligence, analytical thinking, teacher literacy, digital education, ChatGPT, pedagogical approach.